Effects of feeding endophyte-infected tall fescue seeds to stocker Angus steers on retail quality attributes of beef strip steaks. (March 2019) - Holtcamp, Alexander J.; Sukumaran, Anuraj T.; Schnedler, Abigail E.; McClenton, Brandon J.; Kunze, Emery; Calkins, Chris R.; Karisch, Brandi B.; Burnett, Derris D.; Dinh, Thu T.N.
Abstract: The objective of this study was to determine the effects of feeding endophyte-infected tall fescue seeds to Angus steers during the stocker phase on the quality attributes of beef strip steaks during retail display. Endophyte-infected tall fescue seeds had no effect on steak surface lean color, myoglobin forms, proximate composition, thiobarbituric acid reactive substances, aerobic plate count, pH, activity of superoxide dismutase and metmyoglobin reductase, shear force, and sensory attributes ( P  ≥ 0.087). However, lightness, redness, oxymyoglobin percentage, and MRA decreased from 45.01, 32.60, 67.61%, and 9.54 μM/min/g, respectively, on d 0 to 40.11, 21.83, 48.95%, and 2.30 μM/min/g, respectively, on d 7 ( P  ≤ 0.001). Thiobarbituric acid reactive substances were increased by 30% by d 5 ( P  = 0.015) and APC was increased by 0.5 log CFU/g by d 7 ( P  ≤ 0.012). Highlights: Endophyte-infected tall fescue seeds did not affect beef quality attributes during retail display. Beef color stability and MRA were decreased during retail display, concurrent with increased lipid oxidation and off-flavors. Vitamin E in alfalfa and resistance developed by stressed animals might negate the effects of endophyte-infected tall fescue.